Measuring local government transparency - Cruz, Nuno Ferreira da (2016)
Despite the importance of government transparency to promote accountability and prevent maladministration, empirical research has failed to produce proper tools to assess and compare government transparency practices. Most contributions to the topic do not address it from a stakeholder’s perspective, particularly in selecting the indicators to include in transparency indexes. This paper contributes to the debate by developing a municipal transparency index based on information available on local government official websites. The methodological approach borrows insights from the decision analysis literature to structure the index through a participatory process. An application to the Portuguese local government setting is briefly discussed.